Small Beginnings for Great 0pportunities : Lessons Learned from 20 years of Microfinance Projects in IFC - International Finance Corporation (World Bank Group, Washington, DC, 2015)
By increasing access to finance for out-of-reach households and families, microfinance continues to be an essential tool for improving livelihoods at the base of the pyramid. The last 20 years have seen remarkable growth in the microfinance sector. From its early stages in small-scale microenterprise lending, through its commercial expansion to offer savings and a broad array of financial services to low-income customers, to its entry into new markets and incorporation of technological innovations, microfinance is ensuring that an ever-greater number of households have permanent access to a range of high-quality and affordable financial services. The microfinance industry is estimated at $60 to $100 billion globally, where several thousand microfinance organizations reach an estimated 200 million clients, most of whom were not previously served by the formal financial sector. However, 2.5 billion adults still lack access to formal financial services. Financial services for low-income people are an important factor when it comes to poverty reduction, as it enables them to build assets, increase incomes and reduce their vulnerability to economic stress. Moreover, microfinance continues to be an important tool when it comes to empowering women. IFC is the World Bank Group s main investor in microfinance, working with around 300 microfinance institutions (MFIs) and SME-focused financial institutions, which provide financial services in 91 countries. IFC is also one of the leading global investors in terms of volume. In fiscal year 2014, we committed $519 million in 43 projects with MFIs. Our cumulative investment portfolio in microfinance exceeded $3.5 billion, with outstanding commitments of $2.0 billion. In fiscal year 2014, IFC advisory services comprised $74.2 million, representing advisory assistance for 86 projects. This smart book, titled from small beginnings to great opportunities, presents practical lessons learned from the work that authors have been doing on microfinance projects over the last twenty years. From launching the Microfinance Enhancement Facility to help the industry stay afloat during the time of crisis, to working on a project to support microfinance clients to fulfill their housing dreams, these narratives are both engaging and insightful.